PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) DENGAN TEMA DAERAH TEMPAT TINGGALKU UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV C SDN 26 PEKANBARU - Putri Wulan Sari; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research was conducted because of the low achievement on science and social subjects of student class IVC SDN 26 Pekanbaru, KKM set at the school is 75. Out of 24 students that reached the KKM only 11 students (45.83%), while students who not reached the KKM were 13 students (54.16%) with average class of 64.79%. To solve the problem, researcher applied the learning model of problem-based learning. The purpose of this research is to improve students’ achievement with the theme of the area where I live subtheme 1 and subtheme 2 class IVC SDN 26 Pekanbaru with the application of problem-based learning model. After applying problem-based learning model in cycle I mastery learning classical students increased to 62,50% (not complete) and in cycle II mastery learning classical students become 87.50% (complete). First meeting of cycle I, teacher activity had percentage of 60% with good category. At second meeting increased to 85% with very good category. First meeting of cycle II teacher activity increased to 70% with good category. At second meeting it became 85% with very good category. First meeting of cycle I, student activity’s percentage is 60% with enough category. At second meeting become 85% with very good category. First meeting of cycle II, student activity increased to 60% with enough category. At second meeting became 85% with very good category. From this research can be concluded that by applying problem-based learning can improve students’ achievement with the theme of the area where I live subtheme 1 and subtheme 2 class IVC SDN 26 Pekanbaru.Keywords: Problem-Based Learning, Achievement, Curriculum 2013